KEPERCAYAAN INVESTOR PADA SAHAM PT. ANEKA TAMBANG, TBK BERDASARKAN KINERJA KEUANGAN - Subekti, Heni; Musfiyana, Risma; Irawati, Marsha Ayunita (Sekolah Tinggi Ilmu Ekonomi Semarang, 2025)
Abstract. Companies that can survive in the current era of globalization are companies that have healthy financial conditions and strive to convey useful information to stakeholders. This study aims to determine the effect of financial performance on investor confidence in PT. Aneka Tambang, Tbk. The population in this study is secondary data from PT. Aneka Tambang, Tbk's quarterly financial reports totaling 40 data and used as research samples. The analysis method uses multiple linear regression using the SPSS analysis tool. The results of the study stated that the liquidity ratio, profitability ratio and solvency ratio partially have a positive and significant effect on investor confidence. PT. Aneka Tambang, Tbk (ANTM) must be able to improve the values of the liquidity, profitability and solvency ratios to be even better, because these ratios affect investor confidence in investing in PT. Aneka Tambang, Tbk (ANTM), investors will pay attention to the ratio information as a guideline in determining investment choices.